Effect of active versus passive recovery on performance-related outcome during high-intensity interval exercise - Perrier-Melo, R. J.; D'Amorim, I.; Santos, T. M.; Costa, E. C.; Barbosa, R. R.; Costa, M. D. C. (The Journal of Sports Medicine and Physical Fitness, 2021)
INTRODUCTION: It has been suggested that recovery mode may contribute to performance during high-intensity interval exercise. However, there is no consensus regarding the effects of active and passive recovery modes on subsequent performance. The aim of this study was to compare the effect of active versus passive recovery on performance during repeated high-intensity interval exercise. EVIDENCE ACQUISITION: Two reviewers independently conducted a search using the PRISMA systematic approach in three electronic databases (PubMed, Scopus and Cochrane Central) searching for randomized controlled trials (RCTs) comparing the effects of recovery mode on performance (until February 2020). EVIDENCE SYNTHESIS: Twenty-six studies were included for analysis (17 for power output, nine for repeated-sprint ability and two for distance covered). Four studies found higher mechanical performance for passive recovery compared with active recovery. Six out of nine studies reported faster sprinting performance with passive recovery compared to active recovery. Two studies demonstrated that passive recovery resulted in a greater distance covered during intermittent sprint exercise. CONCLUSIONS: This systematic review suggests that performing high-intensity interval exercise with passive recovery results in greater performance when compared with active recovery.